Social skill training and children’s cognitive concentration in rural China: the mediating effect of social information processing skills - Li, Na; Peng, Jin; Sun, Xiaodong; Guo, Shenyang (Frontiers in Psychology, 2025)
BackgroundThe cognitive concentration refers to the learning orientation of children, encompassing the skills, attitudes, and behaviors exhibited by children in their pursuit of knowledge. Enhancing children’s cognitive concentration through targeted social skills training holds notable importance for improving their classroom performance and academic achievement.MethodsDrawing upon the social information processing (SIP) theory and the large-scale trial “Let’s Be Friends (Shaanxi)” program with a randomized controlled experimental design, we employed structural equation modeling (SEM) to analyze the impact mechanism through which social skills training influences children’s cognitive concentration and examine the mediating effect by SIP skills.ResultsThe findings revealed that social skills training significantly enhances both children’s SIP skills and cognitive concentration. SIP skills fully mediate the relationship between social skills training and children’s cognitive concentration. Furthermore, this mediating effect is more pronounced in enhancing boys’ cognitive concentration compared to girls.ConclusionSocial skills training programs focused on enhancing children’s SIP skills represents an effective strategy for augmenting their cognitive concentration.